Modal Budaya dan Modal Sosial dalam Industri Seni Kerajinan Keramik - Purwanto, Antonius (UI Scholars Hub, 2013)
Cultural and social capital is important in the development of industrial cluster of ceramic art craft. This paper describes and explains the role of cultural and social capital in the development of industrial cluster of ceramic art craft in Kasongan. This paper also describes and explains the dynamics of domination and resistance among entrepreneurs in the cluster. By using qualitative research methods show that cultural capital is important for the change of the cluster from the one which produce traditional-functional ceramic to the one which produce artistic ceramic. It is also important for upward social mobility among entrepreneurs. Social capital is important for facilitating economic transaction and for making organization or institution doing a good performance. Bourdieu and Putnam’s concept of social capital are complementary in explaining empirical reality of the cluster. The dominant entrepreneurs have tried to maintain their domination by using of symbolic capital and by developing the cluster in the interest of himself and all entrepreneurs.